(untitled) (Journal of the College of Education for Women, 2024)
Losing a spouse is an event that changes the lives of widows forcing them to navigate a new world filled with sorrow, solitude and unknowns. Over time the way widows have been portrayed has evolved significantly mirroring shifts, in views and cultural norms. Traditionally widows have been depicted as frail and reliant in literature based on the assumption that they lack financial support following their partners passing. However this portrayal fails to acknowledge the toll of widowhood on well being and personal identity. This piece seeks to challenge stereotypes by emphasizing widows’ inner resilience, strength and potential for growth. By comparing how widows are represented in English and Arabic poetry—particularly highlighting instances where Arabic widows are shown as empowered compared to their English counterparts—this study aims to explore the journey of widowhood and question existing narratives of fragility. By showcasing widows’ strength and empowerment in works, this research offers insights, into the psychological landscapes of widows across diverse cultural settings.